10 A simple method to improve the reliability of echocardiography in patients with atrial fibrillation. (May 2019) - Bunting, Karina; Griffith, Michael; Townend, Jonathan; Lip, Gregory; Kirchhof, Paulus; Steeds, Rick; Kotecha, Dipak
Abstract : Introduction: Echocardiography plays an essential role in the management of atrial fibrillation (AF) and the diagnosis of heart failure in these patients. Assessment of systolic and diastolic function is challenging in AF due to the irregular RR interval, resulting in variability from beat to beat. We compared the reproducibility of an index beat (figure 1 ) approach (similar RR intervals for the two prior beats before measurement) versus conventional averaging of three, five and ten consecutive beats in patients with permanent AF. Methods: Consecutive patients were evaluated with a Philips EPIC 7 and X5-1 transducer, and all measurements were analysed offline by an operator blinded to clinical details. A minimum of 30-beat loops were obtained of the apical 2, 3 and 4-chamber, lateral and septal e' and mitral E Vmax. Global longitudinal strain (GLS), Simpson's biplane ejection fraction (EF) and E/e' were calculated and the coefficient of variation determined between 3x index beats, averaged 3 beats, averaged 5 beats and averaged 10 beats. Intra- and inter-observer variability of GLS and E/e' were assessed in 30 and 10 patients respectively, using Bland and Altman analysis. Results: 50 patients with permanent AF and symptoms of heart failure were included, with 46% women and mean age 78±9 years, heart rate 97±19 bpm, NTpro-BNP 1173±647 ng/L, NYHA class 2.5±0.6 and BMI 30±6 kg/m 2 . The index beat method had the lowest coefficient of variation (figure 1 ) for biplane ejection fraction, GLS and E/e' (4.5%, 8.5% and 7.3%), when compared with the average of 3 beats (11.6%, 17.9% and 14.9%), average of 5 beats (11.9%, 17.9% and 14.95) and average of 10 beats (12.3%, 18.5% and 16.2%). GLS intra and inter-observer variability were lowest for the index beat, with small bias and narrow limits of agreement [in brackets]: intra -1.1 [-4.9 to 2.7] and inter -0.7 [-5.4 to 3.9]; verses 3 averaged beats -1.1 [-5.4 to 3.1] and -2 [-6.5 to 4.7]; 5 averaged beats -1.1 [-5.6 to 3.4] and -1.2 [-6.6 to 4.2]; and 10 averaged beats -1.0 [-5.0 to 3.0] and -0.9 [-6.2 to 4.3]. Inter-observer limits of agreement for E/e' were also the narrowest for the index beat method: -1.6 [-0.4 to 3.7]; verses 3 averaged beats -0.6 [-3.5 to 2.2]; 5 averaged beats -0.4 [-3.1 to 2.2]; and 10 averaged beats -0.1 [-2.5 to 2.2]. Conclusion: In patients with AF, an index beat method is more reproducible than the conventional method of averaging multiple consecutive beats. This approach can enhance the reliability of measurements for both systolic and diastolic left ventricular function in patients with AF. Conflict of Interest: Nothing to declare